Finite element modelling of an innovative passive energy dissipation device for seismic hazard mitigation. (1st August 2018) - Titirla, Magdalini D.; Papadopoulos, Panikos K.; Doudoumis, Ioannis N.
Highlights: An innovative passive energy dissipation device, which can be used in new and existing structures. The strengthening level can be easily adjusted and changed during the years. FEM calibration and parametric evaluation that enable robust simulation of the innovative device. Fairly good agreement between experimental and FE simulation. Abstract: Nonlinear finite element analyses of an innovative passive energy dissipation device, referred to herein as CAR1, were conducted to investigate its behavior to dissipate seismic energy. The investigated device belongs to the passive energy dissipation systems, as it doesn't require external power to generate system control forces. It can be used on new or existing structures and can easily be adapted to the particular demands of structures. It can be installed in a variety of ways, including use in either single or cruciate (X) diagonal braces in building frames. Moreover this device has the advantages to provide (i) additional stiffness (ii) dissipation of seismic energy, (iii) as well as control of the axial forces that are developed at the diagonal steel braces. The main part of the device CAR1 is the groups of superimposed blades, which dissipate seismic energy through simultaneous friction and yield. The number and the dimensions of the blades as well as their elastoplastic properties define the constitutive law of the diagonal bars under axial force. To this purpose a finite-element micromodel of the device is formulated and used, by considering contact interface conditions between the blades. The analytical investigation is carried out through an extended comparative parametric study and is focused on the quantitative influence of certain simplified modelling assumptions and several critical modelling parameters on the response of the system. The present paper delineates a set of systematic procedures for finite element model calibration and parametric evaluation that enable robust simulation of the device CAR1 under quasi-static cyclic loading using explicit time-stepping dynamic analysis procedure.